Advances in reconfigurable optical design, metrology, characterization, and data analysis. (23rd February 2021) - Kim, Dae Wook; Smith, Greg A; Dubin, Matt; Lowman, Andrew; Oh, Chang-jin; Quach, Henry; Kang, Hyukmo; Yoo, Hyemin; Trumper, Isaac; Graves, Logan; Aftab, Maham; Davila-Peralta, Christian; et al.
Abstract: Reconfigurable freeform optical systems greatly enhance imaging performance within non-symmetric, compact, and ergonomic form factors. In this paper, several advances improve design, testing, and monitoring of these systems. Specific enhancements include definition of polynomials for fast and efficient parameterizations of vector distributions in non-circular apertures and merit based function optimization. Deflectometry system improvements enable metrology for almost any conceivable optic shape and guide deterministic optical figuring process during the coarse grinding phase by including modulated infrared sources. As a demonstration of these improvements, parametric optimization is tested with the tomographic ionized-carbon mapping experiment, a reconfigurable optical system. Other case studies and demonstrations include metrology of a fast, f/1.26 convex optic, an Alvarez lens, and real-time monitoring of an array of independently-steerable hexagonal mirror segments as well as an induction formed surface and inflatable Mylar mirror.